Flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance

By introducing cellulose, PEO and PMAEDS in the dual-layer capacitor layer of flexible pressure sensors, and Coal-LDH that has been electrochemically activated, the synergistic effect improves the sensitivity and stability of the sensor, solving the yin-transmission channel in the existing technology in existing technology Weak problem.

CN119124408BActive Publication Date: 2025-01-24HEFEI UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411572976.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing capacitive flexible pressure sensors ignore the directional movement of anions when designing the dielectric layer, resulting in the anion transmission channel being weaker than the cation transmission channel, limiting the sensor's sensitivity.

Method used

A flexible pressure sensor is designed based on the synergistic effect of electric double layer capacitance and intrinsic pseudocapacitance. By introducing cellulose as the basic skeleton in the electric double layer capacitance layer, PEO constructs a cation transmission channel, PMAEDS constructs an anion transmission channel, and in the double electric layer capacitance layer Electrochemically activated CoAl-LDH is introduced on the surface of the layer capacitor layer as a pseudocapacitive layer to synergistically improve the sensitivity of the sensor.

Benefits of technology

Effectively enhance the sensitivity, static characteristics and stability of the flexible pressure sensor, and improve the response ability and linearity of the sensor to change the pressure change.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119124408B_ABST
    Figure CN119124408B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of pressure sensors, and discloses a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance, which is a stacked structure, which is an upper electrode layer, an adhesive layer, a pseudocapacitance layer, a double-layer capacitance layer, a pseudocapacitance layer, an adhesive layer and a lower electrode layer from top to bottom, and a packaging layer is wrapped around the flexible pressure sensor as a whole, wherein: the upper electrode layer and the lower electrode layer are a pair of circular electrodes of different sizes, and the lower electrode layer has a larger diameter than the upper electrode layer; the double-layer capacitance layer is in the shape of a disc, and the diameter is the same as that of the upper electrode layer, and a plurality of annular protrusions concentric with the double-layer capacitance layer are symmetrically arranged on the upper and lower surfaces of the double-layer capacitance layer; the pseudocapacitance layer is evenly sprayed on the upper and lower surfaces of the double-layer capacitance layer. The capacitive flexible pressure sensor prepared by the present invention has ultra-high sensitivity, high durability, excellent biocompatibility and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sensors, and in particular relates to a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance. Background Art

[0002] In the fields of wearables, human-computer interaction, etc., flexible pressure sensors have attracted much attention due to their advantages such as being thin, soft, bendable, highly stretchable, and able to accurately feedback pressure signals. Conductive ion gel has good mechanical properties, excellent biocompatibility and strong self-healing ability, and is an important material for the preparation of flexible pressure sensors. However, since the electrodes, dielectric layers, packaging layers and other materials used in the sensor have a certain thickness, when used in scenarios such as small object grasping and pulse wave monitoring, they are prone to distortion, signal loss and other problems due to their own sensitivity limitations. Therefore, an ultra-high sensitivity capacitive pressure sensor has a very broad application prospect.

[0003] Patent application CN110926663A proposes a method for preparing a washable, wearable, highly sensitive pressure sensor. A spinning solution containing palladium and PAN is electrospun, chemically silver-plated and formed into a film as the upper and lower electrodes, and polymers such as plastic and nylon mesh are used as dielectric layer materials to obtain a wearable, washable, highly sensitive, thin and flexible sensor.

[0004] Patent application CN110579296A proposes a double-layer capacitive flexible pressure sensor with an inclined structure enhancement and a manufacturing method, and prepares an inclined microstructure electrode and an electrolyte layer composed of a polymer and an ionic liquid, which has both a wide measurement range and high sensitivity.

[0005] Patent application CN105865667A proposes a capacitive flexible pressure sensor based on a microstructured dielectric layer and a method for preparing the same. By designing dielectric layers with different microstructures and adjusting sensor performance by changing conditions such as the shape, size and distribution of the dielectric layer microstructure, capacitive flexible pressure sensors with different sensitivities and test ranges can be produced.

[0006] Patent application CN111551290A proposes a wearable flexible capacitive pressure sensor and a preparation method thereof. The wire is attached to a polyimide substrate and connected to the electrode. Graphene aerogel with an internal microstructure is used as a conductive filler in the dielectric layer of the flexible capacitive pressure sensor, thereby improving the sensitivity of the sensor.

[0007] In the academic paper "The pseudocapacitance mechanism of graphene / CoAl LDH and its derivatives: Are all the modifications beneficial?" published in the Journal of Energy Chemistry, Jing's team discussed the pseudocapacitance mechanism of CoAl-LDH and its derivatives, and compared the electrochemical performance differences of different derivatives after alkaline etching, sulfonation and phosphorylation treatment, making a great contribution to the application of CoAl-LDH in supercapacitors.

[0008] The academic paper published by Li's group in the journal Chem, titled "Ordered-Vacancy-Induced Cation Intercalation into Layered Double Hydroxides: A General Approach for High-Performance Supercapacitors", electrochemically activated CoFe-LDH to enhance its cation storage performance, opening up a new path for the development of promising and cost-effective electrochemical energy storage materials.

[0009] In the academic paper "Printed and Flexible Capacitive Pressure Sensor with Carbon Nanotubes based Composite Dielectric Layer" published in the journal Micromachines, Guo's team reported the use of a mixture of carbon nanotubes (CNTs) and polydimethylsiloxane (PDMS) with different aspect ratios as a composite dielectric layer to improve the sensitivity of flexible pressure sensors. The prepared sensor has both high sensitivity and high resolution.

[0010] The paper "Multilayer self-filled iontronic pressure sensor with ultrahigh sensitivity and broad sensing range" published by Marouen Zammali's team in the journal Sensors and Actuators A: Physical introduces a multilayer self-filled microstructure in the dielectric layer, which not only greatly improves the sensitivity but also broadens the sensing range.

[0011] Although some progress has been made in improving the sensitivity of ion gel-based flexible pressure sensors, there are still the following shortcomings:

[0012] 1. When designing the dielectric layer hydrogel, existing capacitive flexible pressure sensors usually only focus on the transmission of cations under an external electric field and ignore the directional movement of anions. The undesigned anion transmission channel is weaker than the cation transmission channel, resulting in slower movement of anions under the action of the electric field and lower conductivity of the ion gel, which in turn limits the sensitivity of the sensor.

[0013] 2. Existing capacitive flexible pressure sensors increase the sensitivity of the sensor by adding an ion source into the dielectric layer to form a double layer between the dielectric layer and the electrode. However, the single double-layer capacitance mechanism has a limited amount of interface adsorption due to the repulsion of like charges during adsorption, and the sensitivity of the sensor is therefore limited.

[0014] 3. When designing the dielectric layer, existing capacitive flexible pressure sensors generally introduce cylindrical, conical, pyramidal and other microstructures on the surface, and reduce the initial capacitance and increase the sensitivity by changing the contact area between the dielectric layer and the electrode under pressure. The single microstructure design makes it difficult for the sensor to have both high sensitivity and high linearity.

[0015] 4. Existing capacitive flexible pressure sensors lack adhesives with both high conductivity and high adhesion between the electrodes and the dielectric layer. If the conductivity of the adhesive is too low, the time constant of the entire sensor will be too large, thus affecting the high-frequency characteristics of the sensor. If the adhesion of the adhesive is not good enough, it will easily loosen or fall off between the sensor electrodes and the dielectric layer, resulting in limited reliability and durability of the sensor.

[0016] 5. The existing capacitive flexible pressure sensor packaging layer generally uses organic polymer films such as polyurethane and polyethylene. However, these organic polymer films will irritate human skin during long-term use due to poor air permeability, poor hygroscopicity, and poor biocompatibility, limiting the application of sensors in wearable devices.

[0017] 6. The ion gel and packaging materials of existing capacitive flexible pressure sensors usually use organic polymer materials that are not easy to degrade. The degradation process requires high-temperature treatment or the introduction of strong acids, strong alkalis, and strong oxidants. The degradation cost is high and it is easy to produce harmful substances that damage the natural environment, limiting the widespread application of sensors. Summary of the invention

[0018] In view of the deficiencies in the prior art, the present invention proposes a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance, which effectively improves the sensitivity, static and dynamic characteristics and stability of such flexible pressure sensor.

[0019] To achieve the purpose, the present invention adopts the following technical solution:

[0020] The present invention first discloses a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance. The flexible pressure sensor is a stacked structure, which includes, from top to bottom, an upper electrode layer, an adhesive layer, a pseudocapacitance layer, a double-layer capacitance layer, a pseudocapacitance layer, an adhesive layer, and a lower electrode layer. A packaging layer is wrapped around the flexible pressure sensor as a whole. The upper electrode layer and the lower electrode layer are a pair of circular electrodes of different sizes, and the diameter of the lower electrode layer is larger than that of the upper electrode layer. The double-layer capacitance layer is in the shape of a disc, and its diameter is the same as that of the upper electrode layer; a plurality of circular protrusions concentric with the double-layer capacitance layer are symmetrically arranged on the upper and lower surfaces of the double-layer capacitance layer; the pseudocapacitance layer is evenly sprayed on the upper and lower surfaces of the double-layer capacitance layer.

[0021] Furthermore, the double-layer capacitor layer is made of polyvinyl alcohol (PEO), lithium sulfate (Li2SO4), poly-[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (PMAEDS), N,N-methylenebisacrylamide (MBAA) and cellulose as raw materials, and the mass percentage of each component in the raw materials is: Li2SO4 5%~20%, PMAEDS 5%~10%, MBAA 5%~10%, PEO 10%~20%, and the balance is cellulose. Cellulose is highly cross-linked as the matrix material of the double-layer capacitor layer, which provides good mechanical properties for the double-layer capacitor layer. PEO constructs the Li in the double-layer capacitor layer. + transmission network, greatly improving the Li + The transport speed of the sensor thus reduces the response time. The cross-linked network formed by PMAEDS and MBAA is SO4 2- The transmission channel is formed; the radius difference between anions and cations in Li2SO4 is large, and the ion pairing effect is weak. + Easy to dissociate, the dissociated Li + and SO4 2- In the double-layer capacitor layer, it can move freely and quickly in the double-layer capacitor layer along with the relaxation movement of the cellulose chains and the formed ion channels.

[0022] Furthermore, the total thickness of the double-layer capacitor layer (i.e., including the height of the annular protrusion) is 250-400 μm, the tensile strength is 10-30 MPa, the tensile fracture rate is not less than 50%, and the ionic conductivity is not more than 3×10 -2 S / cm.

[0023] Furthermore, the circular protrusions on the upper and lower surfaces of the double-layer capacitor layer are arranged at equal intervals, and the cross-section of each circular ring is an isosceles trapezoid. The upper side length of the cross-sectional trapezoid of each circular ring increases with the same length difference from the inside to the outside along the radial direction, the lower side length is equal, and the height of each circular protrusion is equal. Furthermore, the radius of the double-layer capacitor layer is 2-5mm, the spacing between each circular protrusion is 50~100μm, the inner circle radius of each circular ring is in the range of 200~1500μm, the lower side length of the cross-sectional trapezoid of each circular ring is 20~40μm, the upper side length is in the range of 10~20μm, and the height of each circular ring is 10~20μm. By introducing the circular microstructure, on the one hand, the initial contact area between the double-layer capacitor layer and the electrode layer is reduced, thereby reducing the initial capacitance, and on the other hand, the change in the effective capacitance interface of the sensor under the action of external pressure is increased, thereby improving the sensitivity of the sensor. The rings of different widths enable the sensor to have consistent capacitance interface changes under different pressure ranges, thereby improving the linearity of the sensor.

[0024] Furthermore, the pseudocapacitor layer is made of CoAl layered double hydroxide (CoAl-LDH) after electrochemical activation treatment, the thickness of the pseudocapacitor layer does not exceed 10-100 μm, and the conductivity at room temperature is not higher than 5×10 -2 S / cm. CoAl-LDH has a two-dimensional layered structure. 2+ and Al 3+ The cation layer, Cl - 、CO3 2- 、NO3 - On the one hand, the Co in the cation layer at high potential 2+ Can lose electrons and oxidize to Co 3+ , the reverse reaction occurs at low potential Co 3+ Reduction to Co 2+ , a redox reaction occurs, causing the capacitance of the dielectric layer to change, introducing a pseudocapacitive component into the sensor. On the other hand, the unique two-dimensional layered structure of CoAl-LDH gives it an ultra-large surface area, providing a large number of adsorption sites. During the electroactivation process, some metal ions in the cationic layer are separated from the lattice, introducing lattice defects, so that under the action of the external electric field, the cationic layer can overcome the electrostatic repulsion and adsorb Li in the double-layer capacitor layer. + , the synergistic effect of double-layer capacitance and pseudocapacitance further improves the sensitivity of the sensor.

[0025] Furthermore, the adhesive layer is made of a mixture of epoxy resin as a sticky matrix, multi-walled carbon nanotubes Ag-MWCNT decorated with silver nanoparticles as a conductive aid, and epoxy resin curing agent, wherein the mass percentage of epoxy resin in the mixture is 61.25% to 78%, the mass percentage of Ag-MWCNT is 5% to 15%, and the mass percentage of epoxy resin curing agent is 17% to 23.75%. The thickness of the adhesive layer is 50μm to 80μm, the tensile fracture rate is not less than 40%, the tensile strength is 1.5 to 9.7MPa, and the conductivity is 1500S / cm to 8000S / cm at room temperature. Multi-walled carbon nanotubes modified with silver nanoparticles are added to the adhesive epoxy resin as a conductive aid to solve the defect of low conductivity of epoxy resin.

[0026] Furthermore, the material used for the upper electrode layer and the lower electrode layer is copper foil. The diameter of the upper electrode layer is 5-20 mm, and the diameter of the lower electrode layer is 0.5-1 mm larger than that of the upper electrode layer. Copper foil has high conductivity, good flexibility and ductility, and provides a good electrical basis for the application of sensors in flexible wearable devices.

[0027] Furthermore, the encapsulation layer is polymerized from cellulose and chitosan, the molecular weight of the chitosan used is not less than 30,000, the viscosity is not less than 400 mPa / s, and the particle size of the cellulose raw material used is 300-400 meshes, and the viscosity is not less than 80,000 mPa / s. The cross-linked network formed by cellulose and chitosan introduces a large number of microporous structures to its surface, making it have good air permeability; the mesh structure of cellulose itself gives it sufficient strength, and its use as an encapsulation layer can increase the service life of the sensor; the large number of hydroxyl groups (-OH) and methoxy groups (-OCH3) in cellulose molecules and chitosan molecules enable them to form hydrogen bonds with water molecules, thus having strong hygroscopicity; in addition, cellulose and chitosan have excellent biocompatibility, and as an encapsulation layer, the sensor can be used in close contact with the skin for a long time to avoid damage to the skin; cellulose and chitosan, as natural biomaterials, can be naturally degraded and have excellent environmental sustainability.

[0028] The present invention further provides a method for preparing the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance, comprising the following steps:

[0029] Step 1: Prepare double-layer capacitor layer

[0030] PEO, PMAEDS, MBAA and cellulose were added to DMF, and magnetically stirred at 60-80°C for 2-3 hours until the solution became clear and transparent; then Li2SO4 was added to the solution, and stirring was continued for 2-3 hours until the solution was evenly mixed and became white and viscous, thereby obtaining a flexible ion gel material;

[0031] The flexible ion gel material is injected into a mold of a double-layer capacitor layer, cured at 60-80° C., and then demoulded to obtain a double-layer capacitor layer.

[0032] Step 2: Preparation of pseudocapacitor layer

[0033] CoAl-LDH was used as the working electrode, calomel electrode as the reference electrode, and graphite electrode as the counter electrode to form a three-electrode system. Using an electrochemical workstation, the system was cycled 5 times at 0-5V at a rate of 50-200mV / s in a 0.1-0.5mol / L KOH solution to activate CoAl-LDH and generate lattice defects, thereby obtaining activated CoAl-LDH.

[0034] After grinding the activated CoAl-LDH, ultrasonically dispersed it in deionized water at a concentration of 0.05-0.2 g / mL to obtain a suspension;

[0035] The obtained suspension is evenly sprayed on the upper and lower surfaces of the double-layer capacitor layer and dried at 50-80°C to remove water. The spraying and drying are repeated 3-5 times to form pseudocapacitor layers on the upper and lower surfaces of the double-layer capacitor layer.

[0036] Step 3: Preparation of bonding layer and electrode layer

[0037] Add carboxylated multi-walled carbon nanotubes COOH-MWCNT to DMF, then add sodium dodecyl sulfate SDS to improve dispersibility, and after ultrasonication for 1-3 hours, heat to 50-80°C, add AgNO3 aqueous solution dropwise under stirring, continue to keep warm and stir for 1-3 hours after the addition is completed, and then stand for 24-48 hours (no heating or stirring required); finally, centrifuge the reaction mixture, wash with deionized water, and vacuum dry at 40-60°C for 6-8 hours to obtain Ag-MWCNT; wherein the mass ratio of COOH-MWCNT, SDS and AgNO3 is 3:0.5-1:4-5;

[0038] Ag-MWCNT and epoxy resin were mixed using a high-speed mechanical mixer at a speed of 1000-2000 rpm for 0.5-1.5 h, and then ultrasonicated for 0.5-1.5 h to obtain an adhesive layer solution;

[0039] The bonding layer solution is dried at 80-120° C. for 1-2 hours to make the solution viscous to obtain bonding layer ink; the bonding layer ink is uniformly mixed with an epoxy resin curing agent and then coated on copper foils serving as an upper electrode layer and a lower electrode layer to form a bonding layer; and the upper electrode layer and the lower electrode layer are then fixed on the pseudocapacitor layer using the bonding layer.

[0040] Step 4: Prepare the encapsulation layer

[0041] The cellulose powder is added to deionized water, heated and stirred at 70-90°C until dissolved, and then chitosan of the same mass as the cellulose powder is added, and then hydrochloric acid with a mass concentration of 10% is added to adjust the pH to 1-2, and the heating and stirring are continued for 2-4 hours, and the mixture is introduced into a flat mold and dried at 70-100°C for 1-3 hours to completely remove the water and hydrochloric acid therein, and then washed with deionized water and ethanol in turn and air-dried to obtain an encapsulation film;

[0042] A coating rod is used to evenly coat a layer of a mixture of epoxy resin and epoxy resin curing agent on the surface of the upper electrode layer and the lower electrode layer respectively, and then a packaging film is adhered to the outside as a whole. Pressure is applied by a press until it is fully bonded, thus completing the packaging and obtaining a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0044] 1. The present invention introduces cellulose as the basic skeleton in the double-layer capacitor layer. On the one hand, the long molecular chain of high-polymerization cellulose makes Li + and SO4 2- The ability to transmit in the matrix network by means of its chain extension and contraction makes the double-layer capacitor matrix have a higher ion mobility, thus improving the sensitivity of the sensor. On the other hand, the cross-linked network formed by cellulose provides excellent mechanical properties for the dielectric layer, making the sensor have excellent repeatability.

[0045] 2. The present invention introduces PEO into the double-layer capacitor layer to construct a cation transport channel. Under the action of an external electric field, the CO bond in PEO can react with Li + Combine and implement Li + Directed transport along the direction of the polymer chain, PEO constructs the Li + transmission channel, making Li + It has a faster migration rate in the double-layer capacitor layer, which improves the cation mobility of the double-layer capacitor layer, making it easier for cations to migrate to the electrode surface under the action of the electric field, thereby improving the sensitivity of the sensor.

[0046] 3. The present invention introduces PMAEDS into the double-layer capacitor layer to construct an anion transmission channel. PMAEDS has a positively charged quaternary ammonium group that can react with SO4 2- Combine and transport it along the polymer chain to build SO4 2- The transmission channel makes SO4 2- It has a faster migration rate in the ion gel, which improves the anion mobility of the dielectric layer. In addition, the negatively charged sulfonate group -SO3 in PMAEDS can react with Li +Combined and transported on the polymer chain, further increasing the Li + The synergistic effect of PEO and PMAEDS makes the double-layer capacitor layer more + The hydrogel has a larger dielectric constant, which improves the sensitivity of the sensor.

[0047] 4. The present invention introduces electrochemically activated CoAl-LDH on the surface of the double-layer capacitor layer, and utilizes the oxidation-reduction of metal ions (Co 2+ -Co 3+ ) and the accompanying OH - The adsorption and desorption of the pseudocapacitor component is introduced into the dielectric layer (the dielectric layer in the present invention represents the double-layer capacitor layer and the pseudocapacitor layer). Li2SO4 is introduced as a lithium ion source in the double-layer capacitor layer, and the double-layer capacitor component is introduced into the dielectric layer. Lattice defects are introduced into CoAl-LDH by electrochemical activation, so that Li + During the voltage cycle, adsorption and desorption can be performed on the CoAl-LDH cation layer, thereby realizing the synergistic effect of the pseudocapacitive component and the double-layer capacitance component. The introduction of the pseudocapacitive component and the synergistic effect of the two capacitance components make the double-layer capacitance layer of the present invention have a larger unit charge density than the pure ion gel dielectric layer, thereby increasing the capacitance change of the sensor under pressure and improving the sensitivity of the sensor.

[0048] 5. The present invention adopts a casting process and a mold forming method to introduce annular raised microstructures with different widths on the surface of the double-layer capacitor layer. On the one hand, the introduction of the microstructure reduces the initial capacitance of the sensor, making the sensor more sensitive to the capacitance change of the dielectric layer. On the other hand, as the applied pressure increases, the contact area between the electrode and the dielectric layer increases, resulting in a gradual increase in the interface capacitance between the electrode and the dielectric layer. The introduction of the annular raised microstructure increases the sensitivity of the sensor. The rings of different widths allow the sensor to have consistent capacitance interface changes under different ranges of pressure, thereby improving the linearity of the sensor.

[0049] 6. The present invention sets a multi-walled carbon nanotube Ag-MWCNT / epoxy resin adhesive decorated with silver nanoparticles between the dielectric layer and the electrode. The large amount of oxygen atoms in the epoxy resin provides adsorption sites, which makes it have a strong interface adsorption effect and strong adhesion, so that the sensor is not prone to desorption of the electrode and the dielectric layer during long-term use, thereby improving the consistency and stability of the sensor. The introduction of Ag-MWCNT forms a conductive network in the epoxy resin, greatly improving the conductivity of the adhesive, thereby reducing the time constant of the sensor and optimizing the hysteresis characteristics of the sensor. PEO is used to construct Li in the double-layer capacitor layer. + Transmission network, making Li+ It has a faster migration rate, which reduces the delay of the sensor and optimizes the hysteresis characteristics of the sensor.

[0050] 7. The encapsulation layer of the present invention is made of cellulose and chitosan. The reticular structure of cellulose itself makes it have sufficient strength. Using it as an encapsulation layer can increase the service life of the sensor. Both cellulose and chitosan are biomass materials with good biocompatibility. The network formed by cross-linking cellulose and chitosan makes it have good air permeability. The large number of hydroxyl and methoxy groups on the molecular chain provide it with good hygroscopicity. It will not irritate human skin during long-term use, expanding the application range of flexible pressure sensors.

[0051] 8. The organic polymers used in the present invention, such as PEO, PMAEDS, MBAA, cellulose, etc., can be naturally degraded or greenly degraded in a simple manner, and will not produce substances harmful to the environment. All reagents such as Li2SO4 and CoAl-LDH are non-toxic and harmless to the human body. The entire sensor has strong environmental adaptability and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The overall structure diagram of a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance provided by the present invention.

[0053] Figure 2 A schematic diagram of a mold for making a double-layer capacitor layer and the microstructure of the produced double-layer capacitor layer.

[0054] Figure 3 The conductive channel formed by PEO and Li + Schematic diagram of the interaction.

[0055] Figure 4 Conductive channels formed by PMAEDS and MBAA and SO4 2- and Li + Schematic diagram of the interaction.

[0056] Figure 5 Schematic diagram of the structure of CoAl-LDH.

[0057] Figure 6 Schematic diagram of the pseudocapacitive effect of CoAl-LDH.

[0058] Figure 7 The Li + Schematic diagram of the adsorption and desorption principle in the activated CoAl-LDH lattice.

[0059] Figure 8The stress-strain curves of Ag-MWCNT / epoxy resin conductive adhesive layer strips with the same cross-sectional area and length at different Ag-MWCNT concentrations.

[0060] Fig. 9 The resistance change curve of the Ag-MWCNT / epoxy resin conductive adhesive layer strip with the same cross-sectional area and length under different Ag-MWCNT concentrations.

[0061] Fig.10 It is a comparison chart of stress-capacitance change rate curves of the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance (curve corresponding to S1) and the pressure sensor without a pseudocapacitance layer (curve corresponding to S2) produced in Example 1 under a stress range of 500KPa.

[0062] Fig.11 The frequency characteristic curves of the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance manufactured in Example 1 at different frequencies.

[0063] Fig.12 This is a repetitive characteristic curve of the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance manufactured in Example 1. DETAILED DESCRIPTION

[0064] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0065] The PEO used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (powder, Mw~100000).

[0066] PMAEDS used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 98.0%).

[0067] MBAA used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 99.0%).

[0068] Li2SO4 used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 98.0%).

[0069] The CoAl-LDH used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0070] The DMF used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 99.5%).

[0071] The carboxylated multi-walled carbon nanotubes (MWCNT-COOH) used in the following examples were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 99.9%).

[0072] AgNO3 used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (40 mg / mL).

[0073] The epoxy resin used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0074] Sodium dodecyl sulfate (SDS) used in the following examples was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. (AR, 92.5-100.5%).

[0075] The epoxy resin curing agent 593 used in the following examples was purchased from Zhengzhou Xiangzhida Chemical.

[0076] The cellulose used in the following examples was purchased from Hebei Zhicheng Cellulose Co., Ltd. (viscosity 100000 mPa / s).

[0077] The chitosan used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (Mw ~ 30000, viscosity > 400 mPa / s).

[0078] The hydrochloric acid used in the following examples was purchased from Nanjing Reagent (AR).

[0079] Example 1

[0080] like Figure 1 As shown, the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance provided in this embodiment is a stacked structure, which includes, from top to bottom, an upper electrode layer 4a, an adhesive layer 3, a pseudocapacitor layer 2, a double-layer capacitance layer 1, a pseudocapacitor layer 2, an adhesive layer 3 and a lower electrode layer 4b, and a packaging layer 5 is wrapped around the flexible pressure sensor as a whole.

[0081] The preparation of the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance in this embodiment includes the following steps:

[0082] Step 1: Double layer capacitor layer

[0083] 1 g PEO, 0.5 g MBAA, 0.5 g PMAEDS, and 5 g cellulose were added to 20 mL DMF and magnetically stirred at 80 °C for 2 hours until the solution was clear and transparent with no obvious particles at the bottom of the beaker; then 1 g Li2SO4 was added to the solution and stirred for another 2 hours until the solution was evenly mixed and became white and viscous, thereby obtaining a flexible ion gel material.

[0084] The prepared flexible ion gel material was cast into the mold by 3D printing a mold containing a circular microstructure, and dried and cured in a constant temperature box at 70°C for 4 hours. After demolding, a double-layer capacitor layer was obtained. According to the test, the total thickness of the double-layer capacitor layer obtained in this embodiment is 317μm, the tensile strength is 21.6MPa, the tensile fracture rate is 60.7%, and the ionic conductivity is 1.3×10 -2 S / cm.

[0085] Step 2: Preparation of pseudocapacitor layer

[0086] CoAl-LDH was used as the working electrode, calomel electrode as the reference electrode, and graphite electrode as the counter electrode to form a three-electrode system. Using an electrochemical workstation, the CoAl-LDH was activated to produce lattice defects by cycling 5 times at a rate of 100 mV / s in a 0.1 mol / L KOH solution to obtain activated CoAl-LDH. 0.5 g of activated CoAl-LDH was ground and dispersed in 5 mL of deionized water, and ultrasonically treated for 30 minutes to obtain a stable suspension.

[0087] The suspension was evenly sprayed on the upper and lower surfaces of the double-layer capacitor layer and dried in a thermostat at 80°C to remove water. The spraying and drying were repeated three times, so that pseudocapacitor layers were formed on the upper and lower surfaces of the double-layer capacitor layer. The test showed that the ionic conductivity of the pseudocapacitor layer obtained in this embodiment was 2.7×10 -2 S / cm, thickness is 78μm.

[0088] Step 3: Preparation of bonding layer and electrode layer

[0089] 300 mg COOH-MWCNT was mixed into 250 mL DMF, and then 100 mg SDS was added. The mixture was ultrasonically treated for 2 hours, heated to 60°C, and 20 mL of 20 mg / mL AgNO3 aqueous solution was added dropwise under stirring. After the addition was completed, the mixture was kept warm and stirred for 1 hour, and then allowed to stand for 24 hours. Finally, the reaction mixture was centrifuged, washed with deionized water, and dried under vacuum at 50°C for 8 hours to obtain Ag-MWCNT.

[0090] 1 g of Ag-MWCNT was mixed with 10 g of epoxy resin using a high-speed mechanical mixer at a rotation speed of 1500 rpm for 30 minutes, and then ultrasonicated for 1 hour to obtain an adhesive layer solution.

[0091] Take a piece of 5cm×5cm×0.1mm copper foil, set the upper electrode size to 4mm radius and the lower electrode size to 5mm radius in the laser cutting machine, and set the laser cutting machine to cut the copper foil at 80W cutting power, 10mm / s cutting speed and 125mm focal length. After cutting, clean the surfaces of the two electrode layers with deionized water and anhydrous ethanol once, and after drying, the upper electrode layer and the lower electrode layer can be obtained.

[0092] The bonding layer solution was dried at 100°C for 1 hour to make the solution in a non-fluid viscous state to obtain bonding layer ink; the bonding layer ink was evenly mixed with 2.5g of epoxy resin curing agent 593, and then coated on copper foils serving as the upper electrode layer and the lower electrode layer, respectively, to form bonding layers; and then the upper electrode layer and the lower electrode layer were fixed on the pseudocapacitor layer using the bonding layer.

[0093] According to tests, the thickness of the adhesive layer obtained in this embodiment is 67 μm, the tensile fracture rate is 68.2%, the tensile strength is 3.9 MPa, and the electrical conductivity at room temperature is 6742 S / cm.

[0094] Step 4: Prepare the encapsulation layer

[0095] Take 5g of cellulose powder with a particle size of 350 mesh and a viscosity of 100000mPa / s and add it to 20mL of deionized water. After heating and stirring at 80°C until dissolved, add 5g of chitosan, and then add hydrochloric acid with a mass concentration of 10% to adjust the pH to 1-2. Continue heating and stirring for 3 hours to complete the reaction. Introduce it into a flat mold and dry it at 80°C for 2 hours to completely remove the moisture and hydrochloric acid therein. Wash it with deionized water and ethanol in turn and air-dry it to obtain an encapsulation film.

[0096] Use a coating rod to evenly coat a layer of a mixture of epoxy resin and epoxy resin curing agent 593 on the surface of the upper electrode layer and the lower electrode layer respectively, and then adhere the packaging film to the outside as a whole, and then apply pressure through a press until it is fully bonded to complete the packaging, forming a packaging layer wrapped around the flexible pressure sensor, and obtaining a flexible pressure sensor based on the synergistic effect of double layer capacitance and intrinsic pseudocapacitance.

[0097] Figure 2A schematic diagram of the microstructure of a mold for making a double-layer capacitor layer and the double-layer capacitor layer produced. By introducing a regular annular protrusion microstructure on the surface of the double-layer capacitor layer, on the one hand, the rate of change of the contact area between the double-layer capacitor layer and the electrode when subjected to pressure is increased, thereby improving the sensitivity and responsiveness of the sensor. On the other hand, the circular rings of different widths enable the sensor to have consistent capacitance interface changes under pressures in different ranges, thereby improving the linearity of the sensor. Specifically, in this embodiment, the radius of the double-layer capacitor layer is 4 mm, the spacing between each annular protrusion is 100 μm, the inner radius of each circular ring is 1000 μm, 1100 μm, and 1200 μm, respectively, and the lower side length of the trapezoidal cross section of each circular ring is 20 μm, the upper side length is 10 μm, and the height of each circular ring is 10 μm.

[0098] Figure 3 The conductive channel formed by PEO and Li + Schematic diagram of the interaction, the abundant O atoms on the PEO long chain are Li + Provides adsorption sites, with the extension and contraction of PEO chains and the action of electric field Li + It can move between different O atoms on the PEO chain and between PEO chains, realizing the Li + Directed transport on PEO to construct Li + transmission channel.

[0099] Figure 4 Conductive channel formed by PMAEDS and MBAA and SO4 2- and Li + Schematic diagram of the interaction. The quaternary ammonium ions in PMAEDS can interact with SO4 2- Combined with the cellulose chain, the SO4 2- transmission channel. At the same time, the sulfonate group (SO3 - ) can adsorb and transport Li + , and PEO synergistically constructed Li + MBAA, as a cross-linking agent, stabilizes the ion transport channel formed by PMAEDS.

[0100] Figure 5 The schematic diagram of the structure of CoAl-LDH. CoAl-LDH is a two-dimensional layered structure, with metal ions and hydroxide (OH - ) are packed in an approximate hexagonal manner to form the cation layer of CoAl-LDH, and carbonate (CO3 2- ) balances the charge of the cation layer. The cation layers repel each other due to electrostatic repulsion and CO3 2-The positions of CO3 2- and Li + Ability to move in and out between floors.

[0101] Figure 6 Schematic diagram of the pseudocapacitive effect of CoAl-LDH. Under the action of an external electric field, Co transforms between +2 and +3 valences, accompanied by a small amount of OH - and CO3 2- The adsorption and desorption of ions lead to charge accumulation in the pseudocapacitive layer.

[0102] Figure 7 The Li + Schematic diagram of the adsorption and desorption principle in the activated CoAl-LDH lattice. The surface of CoAl-LDH after electrochemical treatment is affected by H + The desorption of Li + The embedding of Li provides a vacancy, + The activated CoAl-LDH relies on electrostatic interaction rather than chemical bonding, and can achieve Li + The adsorption and desorption of double-layer capacitance are realized, realizing the synergistic effect of double-layer capacitance and pseudocapacitance.

[0103] Figure 8 and Fig. 9 The stress-strain curves and resistance change curves of Ag-MWCNT / epoxy resin conductive adhesive layer strips of the same length and cross-sectional area under different Ag-MWCNT concentrations are shown respectively. When preparing the conductive adhesive layer solution according to the above step 3, the total mass of the solution is controlled to be 10g, and the amount of Ag-MWCNT added is adjusted to be 0.5g, 0.8g, 1g, 1.2g, 1.5g, respectively, to form conductive adhesive layer solutions with mass fractions of 5%, 8%, 10%, 12%, and 15%, respectively. After curing, they are cut into strips of 5mm×5mm×1mm for mechanical tensile testing and resistance testing. The sensor is subjected to mechanical tensile testing by a tensile press ZQ990B, and connected to an LCR resistor by a wire for resistance testing, and the obtained stress-strain curves and resistance change curves are plotted respectively.

[0104] Figure 8 The stress-strain curves of the conductive adhesive strips with the same cross-sectional area and length under different Ag-MWCNT contents show that the fracture stress gradually decreases with the increase of Ag-MWCNT content. At the same time, the strain of the conductive adhesive strips gradually decreases under the same stress, indicating that the elasticity of the conductive adhesive strips gradually weakens with the increase of Ag-MWCNT. The stress-strain curves of Ag-MWCNT mass fractions between 8% and 12% are not much different. Fig. 9The resistance change curve of the conductive adhesive layer strip with the same cross-sectional area and the same length under different Ag-MWCNT contents shows that as the Ag-MWCNT content increases, the resistance of the conductive adhesive layer strip gradually decreases. Figure 8 and Fig. 9 It can be seen that when the mass ratio of Ag-MWCNT is between 8% and 12%, the conductive adhesive layer has relatively good adhesion and conductivity, so in the embodiment, an adhesive layer solution with a mass fraction of 10% is selected.

[0105] Fig.10 The stress-capacitance change rate curve comparison of the flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance and the pressure sensor without pseudocapacitance layer under the stress range of 500 kPa is shown in the figure. -1 ), the sensor of this embodiment has 9.47KPa -1 The high sensitivity of 0.014 and the high linearity of 0.814 showed an increase of 42.4% in sensitivity, which indicated that the addition of pseudocapacitive components effectively improved the sensitivity of the sensor.

[0106] Fig.11 The frequency characteristic curves of the flexible pressure sensor based on double-layer capacitance and intrinsic pseudocapacitance at different frequencies in this embodiment are shown in the figure. It can be seen from the curve that the sensor can obtain a stable response under a wide range of loading frequencies, and can still maintain a stable capacitance change at a loading frequency of 10Hz, which is suitable for most application scenarios of flexible pressure sensors.

[0107] Fig.12 This is the repetitive characteristic curve of the flexible pressure sensor based on the synergy of double-layer capacitance and intrinsic pseudocapacitance in this embodiment. The prepared sensor was stretched 1000 times and the capacitance change was recorded. It can be seen from the curve that the sensor still has good repeatability even after multiple stretching.

[0108] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance, characterized in that: The flexible pressure sensor is a stacked structure, which includes, from top to bottom, an upper electrode layer, an adhesive layer, a pseudocapacitor layer, a double-layer capacitor layer, a pseudocapacitor layer, an adhesive layer and a lower electrode layer, and a packaging layer is wrapped around the flexible pressure sensor as a whole; The upper electrode layer and the lower electrode layer are a pair of circular electrodes of different sizes, and the lower electrode layer has a larger diameter than the upper electrode layer; The double-layer capacitor layer is disc-shaped, with the same diameter as the upper electrode layer; a plurality of annular protrusions concentric with the double-layer capacitor layer are symmetrically arranged on the upper and lower surfaces of the double-layer capacitor layer; and the pseudocapacitor layer is evenly sprayed on the upper and lower surfaces of the double-layer capacitor layer.

2. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1, characterized in that: The double-layer capacitor layer is made of Li2SO4, PMAEDS, MBAA, PEO and cellulose as raw materials, and the mass percentage of each component in the raw materials is: Li2SO4 5%~20%, PMAEDS 5%~10%, MBAA 5%~10%, PEO 10%~20%, and the balance is cellulose.

3. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1 or 2, characterized in that: The total thickness of the double-layer capacitor layer is 250-400 μm, the tensile strength is 10-30 MPa, the tensile fracture rate is not less than 50%, and the ionic conductivity at room temperature is not more than 3×10 -2 S / cm.

4. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1 or 2, characterized in that: The circular protrusions on the upper and lower surfaces of the double-layer capacitor layer are arranged at equal intervals, and the cross-section of each circular ring is an isosceles trapezoid. The upper side lengths of the cross-section trapezoids of each circular ring increase with the same length difference from the inside to the outside along the radial direction, and the lower side lengths are equal, and the heights of the circular protrusions are equal.

5. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 4, characterized in that: The radius of the double-layer capacitor layer is 2-5 mm, the spacing between each circular protrusion is 50-100 μm, the inner radius of each circular ring is in the range of 200-1500 μm, the lower side length of the trapezoidal cross-section of each circular ring is 20-40 μm, the upper side length is in the range of 10-20 μm, and the height of each circular ring is 10-20 μm.

6. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1, characterized in that: The pseudocapacitor layer is made of CoAl layered double hydroxide (CoAl-LDH) after electrochemical activation treatment; the thickness of the pseudocapacitor layer does not exceed 10-100 μm, and the conductivity is not higher than 5×10 -2 S / cm.

7. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1, characterized in that: The adhesive layer is made of a mixture of epoxy resin as a sticky matrix, multi-walled carbon nanotubes Ag-MWCNT decorated with silver nanoparticles as a conductive additive, and an epoxy resin curing agent, wherein the mass percentage of the epoxy resin in the mixture is 61.25% to 78%, the mass percentage of the Ag-MWCNT is 5% to 15%, and the mass percentage of the epoxy resin curing agent is 17% to 23.75%; the thickness of the adhesive layer is 50μm to 80μm, the tensile fracture rate is not less than 40%, the tensile strength is 1.5 to 9.7MPa, and the conductivity at room temperature is 1500S / cm to 8000S / cm.

8. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1, characterized in that: The material used for the upper electrode layer and the lower electrode layer is copper foil.

9. The flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to claim 1, characterized in that: The encapsulation layer is polymerized from cellulose and chitosan, the molecular weight of the chitosan used is not less than 30,000 and the viscosity is not less than 400 mPa·s, the particle size of the cellulose raw material used is 300-400 meshes and the viscosity is not less than 80,000 mPa·s.

10. A method for preparing a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: Prepare double-layer capacitor layer PEO, PMAEDS, MBAA and cellulose were added to DMF, and magnetically stirred at 60-80°C for 2-3 hours until the solution became clear and transparent; then Li2SO4 was added to the solution, and stirring was continued for 2-3 hours until the solution was evenly mixed and became white and viscous, thereby obtaining a flexible ion gel material; Injecting the flexible ion gel material into a mold of a double-layer capacitor layer, curing at 60-80° C., and demoulding to obtain a double-layer capacitor layer; Step 2: Preparation of pseudocapacitor layer CoAl-LDH was used as the working electrode, calomel electrode as the reference electrode, and graphite electrode as the counter electrode to form a three-electrode system. Using an electrochemical workstation, the system was cycled 5 times at 0-5V at a rate of 50-200mV / s in a 0.1-0.5mol / L KOH solution to activate CoAl-LDH and generate lattice defects, thereby obtaining activated CoAl-LDH. After grinding the activated CoAl-LDH, ultrasonically dispersed it in deionized water at a concentration of 0.05-0.2 g / mL to obtain a suspension; The obtained suspension is sprayed evenly on the upper and lower surfaces of the double-layer capacitor layer, and dried at 50-80°C to remove water. The spraying and drying are repeated 3-5 times, so that pseudocapacitor layers are formed on the upper and lower surfaces of the double-layer capacitor layer. Step 3: Preparation of bonding layer and electrode layer Add carboxylated multi-walled carbon nanotubes COOH-MWCNT to DMF, then add sodium dodecyl sulfate SDS, and after ultrasonication for 1-3 hours, heat to 50-80°C, add AgNO3 aqueous solution dropwise under stirring, continue to keep warm and stir for 1-3 hours after the addition is completed, and then let stand for 24-48 hours; finally, centrifuge the reaction mixture, wash with deionized water, and vacuum dry at 40-60°C for 6-8 hours to obtain Ag-MWCNT; wherein the mass ratio of COOH-MWCNT, SDS and AgNO3 is 3:0.5-1:4-5; Ag-MWCNT and epoxy resin were mixed using a high-speed mechanical mixer at a speed of 1000-2000 rpm for 0.5-1.5 h, and then ultrasonicated for 0.5-1.5 h to obtain an adhesive layer solution; The bonding layer solution is dried at 80-120° C. for 1-2 hours to make the solution viscous to obtain bonding layer ink; the bonding layer ink is uniformly mixed with an epoxy resin curing agent and then coated on copper foils as an upper electrode layer and a lower electrode layer to form a bonding layer; and the upper electrode layer and the lower electrode layer are fixed on the pseudocapacitor layer by using the bonding layer; Step 4: Prepare the encapsulation layer The cellulose powder is added to deionized water, heated and stirred at 70-90°C until dissolved, and then chitosan of the same mass as the cellulose powder is added, and then hydrochloric acid with a mass concentration of 10% is added to adjust the pH to 1-2, and the heating and stirring are continued for 2-4 hours, and the mixture is introduced into a flat mold and dried at 70-100°C for 1-3 hours to completely remove the water and hydrochloric acid therein, and then washed with deionized water and ethanol in turn and air-dried to obtain an encapsulation film; A coating rod is used to evenly coat a layer of a mixture of epoxy resin and epoxy resin curing agent on the surface of the upper electrode layer and the lower electrode layer respectively, and then a packaging film is adhered to the outside as a whole. Pressure is applied by a press until it is fully bonded, thus completing the packaging and obtaining a flexible pressure sensor based on the synergistic effect of double-layer capacitance and intrinsic pseudocapacitance.

Citation Information

Patent Citations

  • Capacitive flexible pressure sensor based on microstructural dielectric layers and preparation method of capacitive flexible pressure sensor

    CN105865667A

  • Double-electric-layer capacitive flexible pressure sensor with enhanced inclined structure and manufacturing method

    CN110579296A

  • Preparation method of washable and wearable high-sensitivity pressure sensor

    CN110926663A

  • Wearable flexible capacitive pressure sensor and preparation method thereof

    CN111551290A

  • Microstructured tactile sensor based on pseudocapacitance principle and preparation method thereof

    CN114112119A